Whole exome sequencing of consanguineous families of clinically diagnosed with neurodevelopmental disorders - Türkgenç, Burcu; Yararbaş, Kanay; Keskin Karakoyun, Hilal; Yeşilyurt, A.; Gezdirici, A.; Tatlı, B.; Akçakaya, N. Handan; Eldeş Hacıfazlıoğlu, Nilüfer; Coşkun, Olcay; Yeşil, Gözde; Ekici, Barış; Yıldırım, Canan; et al. (Springer Nature, 2020)
[Abstract Not Available]
Keywords: Consanguineous Families; Neurodevelopmental Disorders; Exome Sequencing